Serbian Press in the Habsburg Monarchy on the Codification of Law in the Principality of Serbia - Drakić, Gordana; Stanković, Uroš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Тhe paper sheds light on the articles of Serbian press from Habsburg Monarchy related to the codification of law in Serbia. The authors shall discuss the columns of Serbska novina (Magazin za knjižestvo, hudožestvo i modu), Serbske narodne novine, Srbski dnevnik, Svetovid, Srbobran and Napredak in relation with the long way paths to the introduction of civil, criminal and commercial code, as well as codes of civil and criminal procedure for the Principality of Serbia. The trueness of the news shall be subject to examination, and the necessary explanations on the unclear spots of the newspaper articles shall be provided.